Summer and spring elbow rashes is a variant of polymorphous light eruption: confirmation by photoprovocation and histopathology in a series of five cases - de Gálvez, María Victoria; Castillo-Muñoz, Rosa Maria; López-Navarro, Norberto; López-Jiménez, Patricio; Navarrete-de Gálvez, Enrique; Bosch-García, Ricardo; Herrera-Acosta, Enrique; Aguilera, José (Frontiers in Medicine, 2023)
Background: Summer and spring eruption of the elbows is a variant of polymorphous light eruption described on clinical and histopathological grounds; however, to our knowledge, it has not been confirmed by photobiological studies.Objective: The aim of this study was to demonstrate by photobiological studies the involvement of UVA radiation in this variant of polymorphous light eruption located exclusively on the elbows. Methods: A series of 5 patients with polymorphous light eruption lesions on the elbows were included in our study. All patients underwent phototesting and photoprovocation of the skin lesions after exposure to a UVA light source (Philips UVA HPA lamp (400 W). All patients underwent punch biopsy and histopathological and immunohistochemical study with anti-CD123. Results: In all cases, UVA irradiation caused the appearance of skin lesions on the elbows with characteristic polymorphous light eruption. Histological data showed oedema in the superficial dermis and perivascular lymphocytic infiltrate compatible with polymorphous light eruption. Immunohistochemical staining for CD1-23 was negative. Conclusions: For the first time, photobiological photoprovocation studies have demonstrated that, after a series of repeated exposures to UVA radiation, the generation of skin lesions, clinically and histologically compatible with summer and spring eruption of the elbows confirming the elbow rash as a variant of Polymorphous light eruption.